The Role of the Sustainable Development Strategy in Addressing the Impacts of Climate Change in Iraq: A Foresight Vision - albadry , Ammar Saadoon; Badr, Umm Al Banin Ali (The International and Political Journal, 2025)
In recent decades, Iraq has been facing escalating challenges related to climate change, including rising temperatures, declining water resources, increasing desertification, and frequent dust storms. The Sustainable Development Strategy serves as a comprehensive national framework aimed at balancing environmental, economic, and social dimensions to achieve inclusive and sustainable growth. This research analyzes the current state of Iraq’s sustainable development strategy and assesses its effectiveness in addressing climate change challenges. It reviews adopted environmental policies, evaluates national development plans, and explores the main obstacles to practical implementation. Furthermore, the study presents a forward-looking vision for the future of sustainable development in Iraq, proposing strategic pathways to strengthen the country’s climate resilience and achieve long-term sustainability goals by 2030 and beyond.